2017
DOI: 10.1089/jpm.2016.0549
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Comfort Care Order Sets: Aligning Protocols with Current Principles

Abstract: We successfully developed a new comfort care order set at our institutions that can serve as a resource for others. Further evaluation of this order set is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…7,8,13,14 We revised our institution's comfort care order set to create resources to individualize comfort care and align it with current pharmacologic principles. 10 The differences in moral distress between nurses and providers found in our and other studies might be further explained by the different roles these clinicians have in end-of-life care. Providers are more likely to be involved in medical decisionmaking around when to transition to comfort care and managing comfort care orders, including opioids.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…7,8,13,14 We revised our institution's comfort care order set to create resources to individualize comfort care and align it with current pharmacologic principles. 10 The differences in moral distress between nurses and providers found in our and other studies might be further explained by the different roles these clinicians have in end-of-life care. Providers are more likely to be involved in medical decisionmaking around when to transition to comfort care and managing comfort care orders, including opioids.…”
Section: Discussionmentioning
confidence: 54%
“…7,8,13,14 We revised our institution’s comfort care order set to create resources to individualize comfort care and align it with current pharmacologic principles. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few reports of the efficacy of an order set in treating patients at the end of life, both to improve symptom control and to increase adherence to current standards in palliative care treatment [13,14,15]. In a pilot study of children at the end of life, Houlahan et al have reported the use of rapid titration templates, among other strategies, to reduce the burden associated with rapid escalation of pain, dyspnea, and agitation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 50% of Canadians die in acute care hospitals (Statistics Canada, 2018), gaps exist in the care provided to hospitalized patients at the end of life (Bender et al, 2017). End of life (EOL) care has been defined as the support and medical care patients and families receive during the time surrounding death (Razmaria, 2016).…”
Section: Introductionmentioning
confidence: 99%